2015
DOI: 10.1080/00140139.2015.1023851
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the use of observational methods by practitioners when identifying risk factors in physical work

Abstract: Most observational methods for musculoskeletal disorder risk assessment have been developed by researchers to be applied in specific situations, and practitioners could find difficulties in their use in real work conditions. The main objective of this study was to identify the factors which have an influence on how useful the observational techniques are perceived to be by practitioners and to what extent these factors influence their perception. A survey was conducted on practitioners regarding the problems n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
1
26
1
1
Order By: Relevance
“…In contrast, the OWAS method covers both the upper and lower body, and is relatively simple to apply [13]. Furthermore, OWAS is among the most widespread methods used to assess postural risk, which facilitates the comparison of study results with the data reported in the available literature on the subject [14]. The OWAS method is highly reliable [15] and it has been shown to match or surpass the performance of other newer and more detailed postural assessment methods [16].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the OWAS method covers both the upper and lower body, and is relatively simple to apply [13]. Furthermore, OWAS is among the most widespread methods used to assess postural risk, which facilitates the comparison of study results with the data reported in the available literature on the subject [14]. The OWAS method is highly reliable [15] and it has been shown to match or surpass the performance of other newer and more detailed postural assessment methods [16].…”
Section: Methodsmentioning
confidence: 99%
“…Además, para Pedro (2016) y Asensio et al (2012), los métodos de evaluación ergonómica (MEE) se centralizan en la observación de determinados factores como lo son las elevaciones de cargas, las posturas forzadas o la repetitividad de movimientos. De acuerdo con Diego et al (2015), el método RULA permiten evaluar posturas forzadas; según Malchaire et al (2011), los movimientos repetitivos se evalúan con el método OCRA; y, de acuerdo a Diego (2015), el método REBA es el adecuado.…”
Section: Métodos De Evaluación Ergonómicaunclassified
“…This assessment will depend on the type of work performed and its associated risks. The International Ergonomics Association (IEA) and the ISO Technical Committee on Musculoskeletal Disorders have defined a general model, validated by the International Commission on Occupational Health (ICOH), of the main risk factors that should be considered, presenting observation procedures that can be used in their description, classification and evaluation [ 5 , 6 , 7 , 8 ]. Among the most common actions in the workplace are: repetitive work, manual handling of loads, forced postures, and application of force [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most common actions in the workplace are: repetitive work, manual handling of loads, forced postures, and application of force [ 9 , 10 , 11 , 12 ]. This study focuses on evaluation methods for repetitive work and forced postures, since this is where a movement capture system can have the greatest influence: Repetitive movements: The OCRA method (OCcupational Repetitive Action) is the method proposed for a detailed evaluation of work where repetitive movements of the upper limb exist, associating the level of risk with the predictability of the appearance of a disorder in a given time [ 8 , 9 , 10 ]. This method of evaluation considers different factors such as recovery periods, frequency of actions, use of force, presence of uncomfortable postures, and additional factors such as vibrations or inadequate equipment.…”
Section: Introductionmentioning
confidence: 99%